Alternate wetting and drying enhanced the yield of a triple-cropping rice paddy of the Mekong Delta. Issue 4 (4th July 2021) - Arai, Hironori; Hosen, Yasukazu; Chiem, Nguyen Huu; Inubushi, Kazuyuki
ABSTRACT: In the Mekong Delta, triple rice cropping is widely spread. The rice cultivation is characterized by a short cropping period and nearly year-round flooding. Putting the soil under an oxidative condition through changing the water regimes during cropping periods might have a potential to increase the rice yield. To test this potential, an experiment was conducted at a typical triple-cropping farmer's alluvial paddy in a central area of the delta for five years, 15 consecutive cropping seasons. We adopted an intermittent irrigation technique known as alternate wetting and drying (AWD). Under AWD, we irrigated to a depth of 5 cm above the soil surface only when the field water level dropped to 15 cm below the soil surface, with some exceptions. As a control, we prepared a treatment under which the paddy was continuously flooded (CF) except 2 weeks before expected harvest. We also prepared three straw treatments: all raw straw return, all straw-ash return, and no straw return to the paddy. For other field management, we adopted locally conventional methods. Results show that the straw treatment effects on the rice yield were not significant. For water treatments, the soil redox potential under AWD remained higher, in most cases, than that under CF; and the rough rice yield, harvest index, and percentage of ripened grains under AWD respectively became 8.9%, 4.4%, and 3.5% higher ( p < 0.01) than those under CF, with lower N contents in rice grains and 43% less irrigation water use. The increase in rice yield by AWD was found with an increase in harvest index and a decrease in aboveground biomass and nitrogen content, indicating that it was due to the promotion of nutrient translocation in rice by AWD. The effect of AWD was enhanced particularly in the winter–spring cropping season, during which the nighttime temperature was the lowest. This piece of evidence that the rice yield of the delta can be increased simply by introducing AWD has the potential to encourage farmers to take voluntary actions that will also lead to a reduction in methane emission from rice paddies.